Flow pattern-dependent endothelial cell responses through transcriptional regulation. Issue 20 (18th October 2017) - Nakajima, Hiroyuki; Mochizuki, Naoki
ABSTRACT: Blood flow provides endothelial cells (ECs) lining the inside of blood vessels with mechanical stimuli as well as humoral stimuli. Fluid shear stress, the frictional force between flowing blood and ECs, is recognized as an essential mechanical cue for vascular growth, remodeling, and homeostasis. ECs differentially respond to distinct flow patterns. High laminar shear flow leads to inhibition of cell cycle progression and stabilizes vessels, whereas low shear flow or disturbed flow leads to increased turnover of ECs and inflammatory responses of ECs prone to atherogenic. These differences of EC responses dependent on flow pattern are mainly ascribed to distinct patterns of gene expression. In this review, we highlight flow pattern-dependent transcriptional regulation in ECs by focusing on KLF2 and NFκB, major transcription factors responding to laminar flow and disturbed flow, respectively. Moreover, we introduce roles of a new flow-responsive transcriptional co-regulator, YAP, in blood vessel maintenance and discuss how these transcriptional regulators are spatiotemporally regulated by flow and then regulate EC functions in normal and pathological conditions.